Food Safety Regulations: A Virtual Journey Across the Globe - Sanwisate, Phutsadee (My University, 2021)
This report summarizes the online field experiences gained from various mentors during the Summer and Fall of 2020. The author corresponded with a mentor from the European Union (EU) to learn about EU food safety regulations, which are essential in the Thailand-EU agri-food trade, especially in the poultry meat sector. Thai producers must comply with the EU regulations to export products to the EU. The author also corresponded with a mentor from the Kansas Department of Agriculture to learn about Kansas’s food safety regulations related to meat and poultry products. Meat producers in Kansas must follow the Kansas Meat and Poultry Inspection Act. Meat inspectors play an essential role in the safety of meat products in Kansas. The food microbiology laboratory plays a necessary role in regulators’ and food companies’ identification of foodborne pathogens. The author learned about specific laboratory tests used in food safety regulation from a mentor in KSU’s Food Science Institute, as well as from several KDA laboratory officers. The author also learned about the practical application of international food safety standards established by the Codex Alimentarius Commission (Codex) and the World Organization of Animal Health (OIE) related to the poultry sector. Such international standards facilitate trade and enhance the safety of food in global trade. The author’s preceptor, Dr. Justin Kastner, encouraged the author to explore in additional detail selected topics related to food safety and international trade; these included career-development insights from her mentors, peculiar or interesting regulatory issues related to raw milk and seafood, and other interesting topics. The author is grateful for her mentors and her preceptor because the author was able to gain practical, public health knowledge during the midst of the Covid-19 pandemic via this innovative online field experience. The author now understands more about EU food safety regulations, Kansas’s regulations, laboratory tests, and international food safety standards.
Keywords: KDA; EU food safety regulations; Kansas food safety regulations; Thailand's poultry sector; OIE; Codex